Investigating the 'Month of the Year' Effect in India - Raghuram, G. (Indian Journal of Finance, 2017)
The present study divided the past 25 years (from 1990 till the present) into three almost equal time periods and studied the 'month of the year' effect within them in the Indian context by use of the indices - BSE Sensex, BSE 500, BSE MidCap, and BSE SmallCap. The study observed that the 'month of the year' effect is different in each of the three time periods - 'February' effect for the period from January 01, 1990 – December 31, 1998 ; the 'November' effect for the period from January 01, 1999 – December 31, 2006 ; and the 'April' effect for the period from January 01, 2007 – April 01, 2015. However, for a given time period, the same 'month of the year' effect is present for all the indices studied. It was also observed that the 'month of the year' effect is stronger for small caps when compared to large caps.